2023
DOI: 10.1021/acsami.3c01529
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive MOF-Derived Bimetallic Silver and Cobalt Nanocomposite with Enhanced Antibacterial Activity

Abstract: Conventional antibiotic-based treatment of bacterial infections remains one of the most difficult challenges in medicine because of the threat of multidrug resistance caused by indiscriminate abuse. To solve these problems, it is essential to develop an effective antibacterial agent that can be used at a small dose while minimizing the occurrence of multiple resistance. Metal–organic frameworks (MOFs), which are hyper-porous hybrid materials containing metal ions linked by organic ligands, have recently attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…As shown in figure 12, the cell walls of both gram-negative and grampositive bacteria were seriously damaged with the photocatalytic treatment. During the reaction time, reactive oxygen species, predominantly superoxide anion radicals, are generated in the medium, which efficiently attacks the outer shell of the bacterial cell wall and degrades it [59]. Due to the thicker and more tenacious cell wall structure, gram-positive bacteria indicate more persistency against such attacks, and the rate of photoinactivation is lower for these organisms, as revealed in figure 11.…”
Section: Photoinactivation Of E Coli and S Aureus Pathogenic Microorg...mentioning
confidence: 99%
“…As shown in figure 12, the cell walls of both gram-negative and grampositive bacteria were seriously damaged with the photocatalytic treatment. During the reaction time, reactive oxygen species, predominantly superoxide anion radicals, are generated in the medium, which efficiently attacks the outer shell of the bacterial cell wall and degrades it [59]. Due to the thicker and more tenacious cell wall structure, gram-positive bacteria indicate more persistency against such attacks, and the rate of photoinactivation is lower for these organisms, as revealed in figure 11.…”
Section: Photoinactivation Of E Coli and S Aureus Pathogenic Microorg...mentioning
confidence: 99%
“…Iodine (I 2 ) exhibits both antibacterial and virucidal activities and reduces the risk of bacterial resistance. I 2 can be used for sterilization by disrupting bacterial cell walls and protein structures. As for virus inactivation, I 2 solution can rapidly inactivate SARS-CoV-2 in a brief contact time. , The antiviral effect of I 2 is directly related to its content . Moreover, I 2 administration in the URT is deemed to be relatively safe.…”
Section: Introductionmentioning
confidence: 99%
“…30 Kim found that Ag nanoparticles in cobalt-silver bimetallic nanocomposites exhibited strong photothermal conversion efficiency, which synergized with Ag and Co ions to achieve a signicant antimicrobial effect. 31 Although Ag + is effective in killing bacteria as a broad-spectrum antimicrobial agent, the severe biotoxicity also limits its application. Therefore, a bio-safe nanoplatform that not only balances the biocompatibility and toxicity but also possesses controllable photothermal antibacterial behavior is highly required.…”
Section: Introductionmentioning
confidence: 99%